Noninfectious Fever in the Near-Term Pregnant Rat Induces Fetal Brain Inflammation: A Model for the Consequences of Epidural-associated Maternal Fever. Issue 2 (June 2018) - Segal, S.; Pancaro, C.; Bonney, I.; Marchand, J.E.
Abstract : ( Anesth Analg . 2017;125(6):2134–2140) Intrapartum fever of noninfectious etiology during deliveries in women with labor epidural analgesia may adversely affect the developing fetal brain. A proinflammatory cytokine, interleukin (IL)-6, found to be present at increased levels in epidural-associated maternal fever, has been linked to neonatal brain injury. As there is no comprehensive animal model of labor epidural analgesia, the authors of the present study developed a model of noninfectious inflammatory fever in the near-term pregnant rat using IL-6 levels comparable to those found in human patients with labor epidural analgesia-associated fever. They hypothesized that brief administration of IL-6 would induce a core temperature increase in the dams and induce neuroinflammation in the fetus.